Roman Tessellated Mosaics of Caesarea Maritima - Gersht, Rivka (Antiguo Oriente, 2026)
Wall and floor mosaics are among the most bountiful discoveries at Caesarea, yet the number of the Roman tessellated examples, which include floor carpets only, are meager in comparison to the Byzantine ones. Still, the quantity—in regard of quality and motifs variety—is enough for getting a general idea of Roman Caesarea flooring as an index of wealth and of the Caesareans familiarity with contemporary Roman taste and fashions. This article focuses on Roman tessellated mosaics uncovered by the Israel Antiquities Authority (IAA) between 1992 and 2018 in seven private and public Caesarea locations: The Roman Praetorium, a dwelling in insula E1S6, the Dioscuri Domus in insula W2S3, the Roman bathhouse that replaced the domus in insula W2S3, the temple of Augustus and Roma platform façade, Antoninus Pius(?) thermae, and a dwelling in insula E3S4. The assortment includes inscriptions, geometric designs, combinations of geometric and floral motifs, and figural scenes. The mosaics in each of the seven locations are described and compared to their kind in other Roman sites; as the comparisons are numerous a selected amount of examples served to demonstrate the distribution of the patterns and their prevalence. Last to be dealt with are matters concerning direct and indirect sources of inspiration, origin, training and expertise of the mosaicists, and the link between the complexity or simplicity of the tessellated emblemata and the function of the spaces they ornamented.